United States (Journal of Parents and Teachers, 2026)
One of the most important figures in this era of discovery was Alvar Núñez Cabeza de Vaca, who, together with Pánfilo Narváez, reached the Appalachians, where they hoped to find the city of gold and precious stones, but found only miserable villages. Circumstances led them to shipwreck and to live among the Indians as servants and slaves. Cabeza de Vaca learned healing methods from the Indians that even earned him a reputation as a miracle worker. After his adventure in North America, he left for Cadiz in 1540. It is very likely that before 1492, some Nordic navigators had set foot on North American soil without settling there. It was not until the 16th century that some settlements began to be established.
Keywords: North America; discovery; Native Americans; voyage; Spanish